Pelatihan Mindfulness untuk Mengurangi Burnout pada Guru Inklusi Di PKBM Lentera Fajar Indonesia - Zaki Nur Fahmawati; Gitara, Vita Ayu; Wisyastuti (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2023)
Burnout has various impacts in various work professions, especially teachers, interventions carried out to solve stress problems that lead to burnout are so rare. The research was conducted to find out whether mindfulness training had an impact on reducing burnout symptoms in inclusive teachers at PKBM Lentera Fajar Indonesia. The samples Paired T-Test analysis test showed that the post-test average score of the burnout questionnaire with mindfulness training in inclusive teacher was significantly smaller than the pre-test average score.used is a one-group pre-test and post-test design. This study uses an adapted burnout measurement tool. The t-test in the form of a paired sample t-test obtained a significance value of 0.001<0.005. This means, the burnout level before and after being given mindfulness training is not the same. Thus, it can be stated that there is a significant difference between before being given training and after being given mindfulness training, it can be concluded that mindfulness training for burnout in inclusive teachers can reduce the level of burnout in participants.